Severe acute respiratory syndrome and its impact on professionalism: qualitative study of physicians' behaviour during an emerging healthcare crisis. Issue 7457 (2nd June 2004) - Straus, Sharon E; Wilson, Kumanan; Rambaldini, Gloria; Rath, Darlyne; Lin, Yulia; Gold, Wayne L; Kapral, Moira K
Abstract: Objective To explore issues of medical professionalism in the context of severe acute respiratory syndrome (SARS), a new emerging health threat. Design Qualitative interviews analysed with grounded theory methodology. Setting University hospitals in Toronto, Canada, during the SARS outbreak in 2003. Participants 14 staff physicians from divisions of infectious diseases, general internal medicine, and critical care medicine. Results Of 14 attending physicians, four became ill during the outbreak. Participants described their experiences during the outbreak and highlighted several themes about values inherent to medical professionalism that arose during this crisis including the balance between care of patients and accepted personal risk, confidentiality, appropriate interactions between physicians and patients, ethical research conduct, and role modelling of professionalism for junior doctors. Conclusion Despite concerns raised by professional societies about the erosion of professionalism, participants in this study amply demonstrated the necessary qualities during the recent healthcare crisis. However, there were several examples of strained professional behaviour witnessed by the participants and these examples highlight aspects of medical professionalism that medical educators and professional organisations should address in the future, including the balance between personal safety and duty of care.